The Factors Influencing Health Care Associated Infection Among Medical Staff at Buton Utara Hospital - B, Sari Arie Lestari; Nazaruddin (Miracle Journal of Public Health, 2023)
Screening results for HBSAg among 127 employees at RSUD Buton Utara that 7 medical staff and 1 staff positive for HBSAg. This undoubtedly poses a risk of transmission to other employees, patients, and the visiting public. This research aims to examine the factors influencing the prevention of nosocomial infections among medical staff at RSUD Buton Utara. The research design is explanatory research with a cross-sectional study approach. Data were analyzed using the chi-square test to investigate the relationship between independent and dependent variables. Subsequently, logistic regression analysis was used to examine the impact of variables on one another. The population consisted of 129 individuals, and a purposive sample of 127 individuals was drawn. The research findings indicate that there is a relationship between workload, attitudes, healthcare facilities, and medical practices with nosocomial infection prevention at RSUD Buton Utara. However, knowledge was found to have no correlation with nosocomial infection prevention at RSUD Buton Utara. After conducting multiple linear regression analyses, it was determined that workload significantly influences nosocomial infection prevention with a p-value of 0.002. It is recommended to enhance human resources, improve promotion efforts, create a safe and comfortable working environment, and upgrade facilities and infrastructure.